Preliminary study of relating cotton fiber tenacity and elongation with crystallinity. Issue 17 (October 2014) - Liu, Yongliang; Thibodeaux, Devron; Gamble, Gary; Rodgers, James
A fundamental understanding of the relationship between cotton fiber strength (or tenacity)/elongation and structure is important to help cotton breeders modify varieties for enhanced end-use qualities. In this study, the Stelometer instrument was used to measure the bundle fiber tenacity and elongation properties of different cotton fibers. This instrument is the traditional fiber strength reference method and could be still preferred as a screening tool owing to its significant low cost and portability. Fiber crystallinity ( CI IR ) and maturity ( M IR ) were characterized by the previously proposed attenuated total reflection (ATR)-based Fourier transform infrared protocol that has microsampling capability and is suitable for the tiny Stelometer breakage specimens (2 ∼ 5 mg), which cannot be readily analyzed by a conventional X-ray diffraction pattern. Relative to the distinctive increase in fiber tenacity with either CI IR or M IR for Pima fibers ( Gossypium barbadense ), there was an unclear trend between the two for Upland fibers ( G. hirsutum ). Although fiber elongation increases with elevated CI IR and M IR for Pima fibers, it generally decreases as CI IR and M IR increase for Upland fibers. Furthermore, small sets of Upland fibers with known varieties and growth areas were examined, and their responses to both CI IR and M IR are discussed briefly.